Symptoms of and coping strategies for music performance anxiety through different time periods - Irie, Nanako; Morijiri, Yuki; Yoshie, Michiko (Frontiers in Psychology, 2023)
Music performance anxiety (MPA) manifests itself at mental, physiological, and behavioral levels. The present study investigated how the experience of the three levels of symptoms changes over time, and how musicians cope with these temporal changes in MPA symptoms. To this end, we conducted a questionnaire survey in which 38 student musicians freely commented on their experiences of mental and physical changes, as well as their coping strategies for these changes. This was examined during five different time periods around public performance, extending from the beginning of the preparation for a public performance until shortly before the next public performance. The free-text comments obtained from the questionnaire were analyzed thematically and classified into different response themes. We then examined the temporal changes in the frequency of comments on each response theme. We further conducted a semi-structured interview involving eight musicians to explore the responses to the questionnaire in greater detail. We analyzed the contents of the free-text comments obtained from the questionnaire and the interview for each response theme, focusing on the most frequently mentioned sub-themes. The results indicate that musicians started to experience mental MPA symptoms (e.g., negative feelings) as soon as they began to prepare for public performance. To cope with mental symptoms, musicians employed mental strategies such as positive thinking/self-talk and concentration both before and during public performance. The experience of physiological MPA symptoms (e.g., increased heart rate) peaked shortly before public performance and remained throughout performance. To cope with a variety of physiological symptoms, musicians employed physical strategies, especially deep breathing and exercise, shortly before public performance. In contrast, behavioral MPA symptoms (e.g., tremor) were experienced mostly during public performance. Some musicians also reported experiencing the actual impairment of performance quality. To avoid this, musicians employed a variety of practicing techniques (e.g., playing at a slower tempo) during the preparation for public performance and performing techniques (e.g., paying attention to expressions) during public performance. Together, the present findings indicate that mental, physiological, and behavioral symptoms of MPA exhibit differential timelines and that musicians effectively utilize different coping strategies according to the temporal changes in MPA symptoms.